The Peron’s doctrine features and its influence on Argentina’s development - Bredihyn, Andriy (Skhid, 2013)
The given article is devoted to the analysis of the H.D. Peron's doctrine. Complex of the ideological peronist's background is based on political, economic and social components. The short analysis of "19 truth of Peronism" and features of implementation are presented.